Vous êtes sur la page 1sur 13

QUEEN’S COLLEGE

Yearly Examination, 2006-2007


Pure Mathematics
Secondary 6E, S Date : 14 / 6 / 2007
Time : 8:30 - 11:30 am
Instructions :
(1) Answer ALL questions in Section A and Section B.
(2) All workings must be clearly shown.
(3) Unless otherwise specified, numerical answers must be exact.
(4) This paper consists of 4 pages with 200 marks.

FORMULA FOR REFERENCE

sin( A  B )  sin A cos B  cos A sin B

cos( A  B )  cos A cos B sin A sin B

tan A  tan B
tan( A  B ) 
1 tan A tan B

A B A B
sin A  sin B  2 sin cos
2 2

A B A B
sin A  sin B  2 cos sin
2 2

A B A B
cos A  cos B  2 cos cos
2 2

A B AB
cos A  cos B  2 sin sin
2 2

2 sin A cos B  sin( A  B )  sin( A  B)

2 cos A cos B  cos( A  B)  cos( A  B )

2 sin A sin B  cos( A  B)  cos( A  B)

1
Section A : Answer ALL questions in this section. (80 marks)

1. Let   1 be a complex root of x3 – 1 = 0.

(a) Show that 2 +  + 1 = 0.

(b) Let f(x) = x 7  x 6  x 4  2x 2  1 .


Show that x =  is a root of the equation f(x) = 0.
Hence factorize f(x) into two non-linear factors with integral coefficients.
(12 marks)

2. Let , ,  be the roots of the equation x3 – 17x2 + kx – 125 = 0, where  <  < .
If , ,  are in geometric sequence, solve the given equation and also find the value of k.
(10 marks)

3. (a) Expand
 2x  1 n 1   2x  1 in ascending powers of x as far as the term in x3.
2x

(b) By considering the derivative of a geometric series and using (a),


find n if the coefficients of x and x2 in the expression of
1 + 2(2x + 1) + 3(2x + 1)2 + … + n(2x + 1)n-1
are in the ratio of 1 : 6.
(12 marks)
4. (a) By putting x = i in the identity:
x4 + ax3 – x + 2  (x2 + 1) Q(x) + 2x + b, where Q(x) is a polynomial in x ,
determine the numerical values of the real constants a and b.

(b) Find the remainder when x2007 + 1 is divided by (x2 + 1)(x + 1).
(12 marks)

5. A complex number, represented by z = x + y i with x, y  R , may be visualized as a


 x y
2  2 matrix Z =   .
 y x 

(a) Verify that such matrix operations are valid for both addition and multiplication in correspondence
to that of two complex numbers, z1 = x1 + y1i , z2 = x2 + y2i .

(b) Write down without proof, the matrix representation corresponding to (x + y i) -1 ?

(c) What is the complex number that can be multiplied to x + y i in order to rotate it
counter-clockwisely by 90o with respect to the origin ? Write down also its corresponding
matrix of rotation.
(12 marks)

2
6. Prove by mathematical induction that
1 1 1 1 1 1 1 1
1    ...      ... 
2 3 4 2n  1 2n n  1 n  2 2n
is true  n  N .
(10 marks)

7. (a) Prove that k 1  k 1  2 k , kN.

1
(b) Use (a) to prove that  k 1  k 1 , kN.
k

(c) Use (b) to deduce that :

1 1 1
1   ...   n  1  n  2 ,  n  N / {1} .
2 3 n
(12 marks)

Section B : Answer ALL questions in this section. (120 marks)

n
8. (a) By considering the function f(x) = i 1
(ai x – bi)2 , prove the Cauchy-Schwarz Inequality:

“Let a1, a2, …., an ; b1, b2, …., bn be two sets of non-zero real numbers.
2
n  n 2 
n
2
 i i   i   b i 
a b  a
 i1   i1   i1 

a1 a 2 a
Equality sign holds iff   ...  n . ” (14 marks)
b1 b 2 bn

(b) By (a), prove that :


(i)  a, b, c > 0 such that a + b + c = 1,
6a  1  6b  1  6c  1  3 3

 a b c  x y z 
(ii)         9  a, b, c, x, y, z > 0 (16 marks)
 x y z  a b c 

sin 9
9. (a) By using de Moivre’s Theorem write in the form
sin 
a cos8   b cos 6   c cos 4   d cos 2   e , where a, b, c, d, e are constants.
(10 marks)
 2 3 4
(b) Use (a) to find an equation with roots cos 2 , cos 2 , cos 2 and cos 2 .
9 9 9 9

3
(10 marks)

(c) Use (b) to find the values of :


 2 3 4
(i) cos 2  cos 2  cos 2  cos 2
9 9 9 9

 2 3 4
(ii) tan 2  tan 2  tan 2  tan 2 (10 marks)
9 9 9 9

x a b
10. (a) Factorize a x b into 3 linear factors in terms of a, b. (6 marks)
a b x

(b) Use (a) to solve the system of equation:

 x  ay  bz  1

ax  y  bz  a , where a  1, b  1, a + b  –1 . (12 marks)
ax  by  z  b

sin x sin 2 x sin 3x


(c) Use (a) to solve the equation: sin 2x sin x sin 3x  0 for x .
sin 2 x sin 3x sin x

Give your general solutions in radian forms. (12 marks)

11. (a) For any two square matrices A and B of the same order, is it true that

(A + B)2 = A2 + 2AB + B2 ?

If yes, prove it. If no, disprove it by using a counterexample with matrices of order 2.

Tell also the condition on A and B when the equality holds. (7 marks)

1 n a 1 n b 
   
(b) Show that, if A  0 1 n and B  0 1  n
0 0 1  0 0 1 
 

then (A + B)2 = A2 + 2AB + B2. (7 marks)

1 1 0
 
(c) Let P   0 1 1
0 0 1 

(i) Find P2, P3, P4 and guess a formula for Pn, where n  N.

(ii) Prove your guess in (c)(i) by mathematical induction.

(iii) Use (b) to find the inverse of Pn . (16 marks)

4
<< End of Paper >>
Solution
1. (a) Since  is the complex root of 3 – 1 = 0.  3 = 1 …. (1)
3  1 0
2 +  + 1 =   0 ,   1. (4M)
 1  1
(b) f() = 7 + 6 + 4 + 22 + 1
= (3)2  + (3)2 + 3  + 22 + 1
=  + 1 +  + 22 + 1
= 2 (2 +  + 1)
= 0 , by (1). (4M)
 By Factor Theorem, x =  is a root of the equation f(x) = 0.
By (a), f(x) has a factor x2 + x + 1 .
By division, f(x) = (x2 + x + 1) (x5 – x3 + 2x2 – x + 1) . (4A)

       17 ...(1)

2. By Vieta’s theorem,       k ...(2)
   125 ...(3)

(2M)
Since , ,  are in geometric sequence,  = 2 …. (4) (2M)
Subst. (4) in (3),  = 125,
3
 =5 …. (5) (2A)
Subst. (5) in (1),  + 5 +  = 17,   = 12 –  …. (6)
Subst. (5), (6) in (4), (12 – ) = 5 2
,   – 12 + 25 = 0
2

Solving, we get  = 6  11 ( 6  11 is rejected since  <  < ) (1A)


From (6),  = 6  11 . (1A)
Subst. (5) in x3 – 17x2 + kx – 125 = 0, 53 – 17(52) + k(5) – 125 = 0,
 k = 85 (2A)
(Ans) (, , ) = ( 6  11 , 5, 6  11 ) , k = 85. (2A)

 2x  1 n1   2x  1 1  n 1 n 1 
C r  2 x   2 x  1

r
3. (a)  
2x 2 x  r 0 

(2M)

1  n 1 n 1
r
 C
 1  2 x   2 x   C nr 1  2x  
2x  r 2 
n 1
 n   C nr 1  2 x 
r 1

r 2

5
 n  C n2 1  2 x   C 3n 1  2 x   C n4 1  2 x   ...
2 3

 n  2C n2 1x  4C 3n 1 x 2  8C n4 1x 3  ...


(4A)

(b) 1 + 2(2x + 1) + 3(2x + 1)2 + … + n(2x + 1)n-1

=
1 d
2 dx

 2x  1   2x  1 2   2x  1 3  ...   2x  1 n  (2M)

1 d 
 2x  1  2x  1  1
n


2 dx   2x  1  1 

1 d   2 x  1   2x  1 
n 1
  
2 dx  2x 


1 d
2 dx

n  2C n2 1 x  4C 3n 1 x 2  8C n4 1 x 3  ... 


1
2

2C n2 1  8C 3n 1 x  24C n4 1 x 2  ... 
8 n  1 ! 24 n  1 !
 1 : 6  8C3n 1 : 24C n4 1  :
3!  n  2  ! 4! n  3 !
(2A)
1 4
 
6 3 n  2 

 3n – 6 = 24
 n = 10. (2A)

4. (a) x4 + ax3 – x + 2  (x2 + 1) Q(x) + 2x + b …. (1)


Put x = i in (1),
1 – ai – i + 2 = 2i + b  3 –(a + 1) i = 2i + b (3A)
 a = –3, b = 3. (3A)

(b) x2007 + 1 = (x2 + 1) (x + 1) q(x) + Ax2 + Bx + C …. (2) (2M)


Put x = –1 in (2), A – B + C = 0 (1A)
Put x = i in (2), i 2007
+ 1 = A + Bi + C  i 4501+3
+ 1 = (C – A) + Bi (1M)
 –i + 1 = (C – A) + Bi
 C –A=1 …. (3)
B = –1 …. (4)
Solving (2), (3), (4) (A, B, C) = (–1, –1, 0)
The remainder is – x2 –x. (2A)

6
5. (a) z1 = x1 + y1i , z2 = x2 + y2i .
z1 + z2 = (x1 + x2 ) + (y1 + y2 ) i , z1 z2 = (x1 x2 – y1 y2) + (x1y1 + x2 y2 ) i (2A)

 x1 y1   x2 y2 
Z1 =  , Z2 =  
  y1 x1    y2 x 2 

 x1 y1   x 2 y 2   x1  x 2 y1  y 2 
Z1 + Z2 =   +  =   (2A)
  y1 x1    y 2 x 2     y1  y 2  x 1  x 2 

 x1 y1   x2 y 2   x 1 x 2  y1 y 2 x 1 y1  x 2 y1 
Z1 Z2 =     = 
  y1 x1    y2 x 2     x 1 y1  x 2 y1  x 1 x 2  y1 y 2 

(2A)
1
 x y 1 x  y
(b) Z-1 =     
 y x  x 2  y 2  y x 

(2A)

(c) –y + x i = (0 + i) (x + y i) (2M)
 y x   0 1  x y
   
 x  y    1 0   y x 

(2A)

1 1 1 1 1 1 1 1
6. Let u n  1     ...   , vn    ...  , nN.
2 3 4 2n  1 2 n n 1 n  2 2n
Let P(n) be the proposition : un = vn . (2M)
For P(1),
1 1 1 1
u1  1   , v1    u1 = v1 and P(1) is true. (2A)
2 2 11 2
Assume P(k) is true for some k  N , i.e. uk = vk …. (*) (2A)
For P(k + 1),
1 1 1 1 1 1 1
u k 1  1     ...    
2 3 4 2k  1 2k 2 k  1  1 2 k  1

1 1 1 1
 uk    vk   , by (*)
2k  1 2k  2 2k  1 2k  2
1 1 1 1 1
   ...   
k 1 k  2 2 k 2 k  1 2k  2

 1 1 1 1   1 2 
  ...       = vk+1 .
k2 2k 2k  1 2 k  2   k  1 2 k  2 
(4M)
 P(k + 1) is true.

7
By the Principle of Mathematical Induction, P(n) is true  n  N .

7. (a)  k 1  k 1  2
 k 1 2  k  1 k  1  k  1  2k  2 k 2  1  2 k  2 k 2  4 k (2M +
2M)
 k 1  k 1  2 k

1 2 2
(b) By (a),    k  1  k 1 (2M)
k 2 k k 1  k 1

(c) By (b), put k = 2, 3, …, n , (2M)


1
 3 1
2

1
 4 2
3

1
 5 3
4

1
 6 4
5
: :
1
 n  n2
n 1

1
 n 1  n 1
n
Adding the (n – 1) inequalities and add 1 to both sides, (2M)
1 1 1
1   ...   n 1  n  2 . for correct cancellation (2A)
2 3 n

8. (a) (ai x - bi)2  0 i = 1, 2, …, n

n
 n 2 n
 n 2
f(x) =  a x  b 
i 1
i i
2
   a i  x 2  2 a i b i    b i   0
 i1  i 1  i1 
x R

(4M)
n
For the eq. f(x) = 0, we have D  0 and 
i 1
2
a i  0 (for which the equality holds) (4M)

2
 n   n
2 
n
2
2 
 i 1
a i b i   4
 

i 1
a i 


i 1
bi   0

8
2
n   n 2 
n
2
  
 i1
a b
i i  
  i1

a i 
  i1
bi 

(2A)

Equality sign holds  (ai x - bi)2 = 0 , i = 1, 2, …, n


 ai x - bi = 0 , i = 1, 2, …, n
a1 a 2 a
   ...  n (4M)
b1 b 2 bn

(b) (i) Apply Cauchy-Schwarz Inequality to the numbers :


6a  1, 6 b  1 , 6c  1 ; 1, 1, 1 (3M)

 6a  1  6b  1  6c  1  2

   6a  1   6b  1   6c  1  12  12  12 
(3A)
 [6(a + b + c) + 3]  3 (3M)
= 27 since a + b + c = 1.
 6a  1  6b  1  6c  1  3 3

(ii) Apply Cauchy-Schwarz Inequality to the numbers :


a b c x y z
, , ; , , (4M)
x y z a b c
2
 a b c  x y z   a x b y c z 
  1  1  1 2  9
         
 
 x y z  a b c   x a y b z c 
(3A)

9
cos 9  i sin 9   cos   i sin     C 9k  cos   i sin  k
9 n k
9. (a)
k 0

(3M)
 sin 9 = 9 cos8  sin  – 84 cos6  sin3  + 126 cos4  sin5  – 36 cos2  sin7 + sin9  (2A)
sin 9

sin 
= 9 cos8  - 84 cos6  (1 – cos2 ) + 126 cos4  (1 – cos2 )2 - 36 cos2  (1 – cos2 )3+ (1 – cos2 )4
= 256 cos8  – 448 cos6 + 240 cos4  – 40 cos2  + 1 (2M) + (3A)

k
(b) For   , 1  k  4, k  N .
9

sin 9 sin k
 0
sin  k .
sin
9

9
(4M)
k k k k
 256 cos
8
 448 cos 6  240 cos 4  40 cos 2 1 0
9 9 9 9
(2A)

2  2 3 4
 The equation with roots cos , cos 2 , cos 2 and cos 2 is
9 9 9 9
256 x4 – 448 x3 + 240 x2 – 40 x + 1 = 0 (4A)

(c) (i) Sum of roots of the equation in (a) ,


 2 3 4 448 7
cos 2  cos 2  cos 2  cos 2   (2M) +
9 9 9 9 256 4
(2A)

(ii) Put y = 1/x in 256 x4 – 448 x3 + 240 x2 – 40 x + 1 = 0 (2M)


 2 3 4
sec 2 , sec 2 , sec 2 and sec 2 are roots of y4 – 40y3 + 240 y2 – 448 y + 256 =
9 9 9 9
0
4
k
Sum of roots = 
k 0
sec 2
9
= 40 (2A)


 2 3 4 4 k 4  2 k  4 k
tan 2  tan 2  tan 2  tan 2   tan 2    sec  1   sec 2 4
9 9 9 9 k 0 9 k 0  9  k 0 9
= 40 – 4 = 36 (2A)

x a b x a b x a b
R 2 R 2  R 1
10. (a) a x b  ax xa 0   x  a  x  b   1 1 0
R 3 R 3  R 2
a b x 0 bx xb 0 1 1

(3M)

=  x  a  x  b  x  a  b  (3A)

1 a b
(b) D a 1 b  1  a  1  b  1  a  b    a  1 b  1 a  b  1
a b 1

1 a b 1 a a b 1 a b
 
C1 C1  C 2
D1  a 1 b  a 1 1 b   a  1 1 1 b   a  1 2b 2  a  1
b b 1 0 b 1 0 b 1

(2M)

10
1 1 b 0 1 b
C1 C1 C 2 1 b
D2  a a b  0 a b   a  b   a  b  b  ab   b a  b 1  a 
a b
a b 1 ab b 1

(2M)
1 a 1 0 a 1
a 1
 
C1 C1 C3
D3  a 1 a  0 1 a   a  b   a  b  a 2  1   a  b  a  1 a  1
1 a
a b b ab b b

(2M)

x=
D1

 
 a  1 2b 2  a  1  2b 2  a  1   (2A)
D  a  1 b  1 a  b  1  b  1  a  b  1
D2  b a  b  a  1  b a  b 
y=   (2A)
D 1  a  1  b   a  b  1  b  1  a  b  1
D3

 a  b  a  1 a  1   a  b  a  1
z= (2A)
D 1  a  1  b   a  b  1  b  1  a  b  1

(c) (sin x – sin 2x)(sin x – sin 3x)(sin x + sin 2x + sin 3x) = 0 (2M)
(i) sin x – sin 2x = 0  sin (1 – 2 cos x) = 0

 x = n or x = 2n  , where n  Z . (2A)
3

(ii) sin x – sin 3x = 0  - 2 sin x cos 2x = 0



 x = n or x = n  , where n  Z . (2A)
4

(iii) sin x + sin 2x + sin 3x = 0  sin 2 x  2 sin 2 x cos x  0


(2M)
1
 sin 2 x 1  2 cos 2 x   0  sin 2x = 0 or cos 2 x  
2
n 2
 x= or x = 2n  (2A)
2 3
n  2 
Hence the roots of the equations are: , 2n  , 2n  , n 
2 3 3 4
where n  Z . (2A)

11. (a) Not true. (2A)


Counterexample: We need to find any two matrices not commune, AB  BA .

11
1 0  1 1 1 1 1 1  1 0 1 0
   ,    
0 0  0 0   0 0  0 0  0 0   0 0 

(3A)

Condition for equality:


(A + B)2 = (A + B) (A + B) = A2 + AB + BA + B2 = A2 + 2AB + B2
or AB = BA (2A)

(b) By (a), it is sufficient to show that AB = BA. (3M)


1 n a 1 n b  1 0 b  n2  a 
     
AB =  0 1 n 0 1  n  0 1 0  (2A)
0  
 0 1  0
 0 1   0 0 1 

1 n b  1 n a  1 0 a  n2  b
    
BA =  0 1  n  0 1 n  0 1 0  (2A)
0  
 0 1  0 0 1   0 0 1 
So AB = BA .
1 1 0  1 1 0 1 2 1
    
(c) (i) P = 0
2 1 1  0 1 1  0 1 2
0 0 1  0 0 1   0 0 1 

(1A)
1 1 0  1 2 1 1 3 3
    
P = 0
3 1 1  0 1 2   0 1 3
0 0 1  0 0 1   0 0 1 

(1A)
1 1 0  1 3 3  1 4 6
    
P = 0
4 1 1  0 1 3   0 1 4
0 0 1  0 0 1   0 0 1 

(1A)

 1 
1 n n  n  1 
 2 
We guess that P   0
n
1 n  n N. (2A)
0 0 1 
 
 

(ii) Let P(n) be the proposition in (i) above,


P(1) is obviously true. (1A)

 1 
1 k k  k  1 
 2 
Assume P(k) is true for some kN, P   0
k
1 k  (2M)
0 0 1 
 
 

12
For P(k + 1),

 1   1 
1 k k  k  1  1 1 0 1 k 1 k  k  1  k 
 2    2 
P = P P = 0
k+1 k 1 k  0 1 1  0 1 k 1 
0 0 1  0 0 1   0 0 1 
  
   

(2M)


1 k 1
1
 k  1  k  1  1 
 2 
 0 1 k 1 
0 0 1 
 
 

(1A)
 P(k + 1) is true .
By the Principle of mathematical induction, P(n) is true n N.

(iii) In (b), take A = Pn, then B is the inverse of A . i.e. B = (Pn)-1.


1 1
 a= n  n  1 and a – n2 + b = 0  b = n  n  1 (2A)
2 2

 1 
1 n n  n  1 
 2 
 (P ) =  0
n -1 1 n  (3A)
0 0 1 
 
 

13